6
$\begingroup$

For a cell $\square$ in the Young diagram of a partition $\lambda$, let $h_{\square}$ and $c_{\square}$ denote the hook length and content of $\square$, respectively.

Define the functions $$f_n(t):=\sum_{\lambda\vdash n}\prod_{\square\in\lambda}\frac{t+c_{\square}}{h_{\square}}.$$

QUESTION. Does this recurrence hold true? $f_0(t)=1, f_1(t)=t$ and $$(n+2)f_{n+2}(t)=tf_{n+1}(t)+(t^2+n)f_n(t).$$

$\endgroup$
4
  • 1
    $\begingroup$ It seems that $$\sum_{n=0}^\infty f_n(t) x^n = \frac{1}{(1-x)^t (1-x^2)^{\binom{k}{2}}}.$$ $\endgroup$
    – Ira Gessel
    Mar 15 at 20:27
  • 3
    $\begingroup$ The generating function mentioned by Ira Gessel is the specialization of an identity of Littlewood: on one side is the sum of all Schur polynomials in a finite fixed set of variables and on the other side $\prod_{1\leq i\leq n}(1-x_i)^{-1}\prod_{1\leq i<j\leq n}(1-x_ix_j)^{-1}$. So $f_n(t)$ is counting semistandard tableau according to their evaluations (the other meaning of content). $\endgroup$
    – user35313
    Mar 15 at 20:49
  • 3
    $\begingroup$ So together with @user61318's observation, Ira's formula follows from Stanley's Hook Content Formula. By the way for discussion of Littlewood's identity, in fact "bounded" versions of it, see arxiv.org/abs/1506.02755. $\endgroup$ Mar 15 at 20:56
  • 3
    $\begingroup$ The generating function via Littlewood's identity was discussed here mathoverflow.net/questions/263643 $\endgroup$ Mar 15 at 21:15
1
$\begingroup$

Just to complete the picture, here is a wrap up.

The comments by user61318, Sam Hopkins and Gjergji Zaimi justify the generating function by Ira Gessel $$\sum_{n\geq0}f_n(2t)x^n=\frac1{(1-x)^{2t}(1-x^2)^{t(2t-1)}},$$ where I replace $t\rightarrow 2t$ for convenience. Expanding the RHS into a Taylor series, we get $$f_n(2t)=\sum_{k=0}^{\lfloor\frac{n}2\rfloor}\binom{2t^2-t-1+k}k\binom{2t-1+n-2k}{n-2k}.\tag1$$ So, we derive the recurrence $(n+2)f_{n+2}(2t)-2tf_{n+1}(2t)-(4t^2+n)f_n(2t)=0$ for the RHS of (1). Denote the summand in (1) by $F(n,k)$ (suppressing $t$) and introduce the function $$G(n,k)=-2k\binom{2t^2-t-1+k}k\binom{2t+1+n-2k}{n-2k+2}.$$ It's routine to check (preferably using a symbolic software) that \begin{align*} &(n+2)F(n+2,k)-2tF(n+1,k)-(4t^2+n)F(n,k) \\ =&G(n,k+1)-F(n,k). \tag2 \end{align*} Summing both sides of (2) over all integers and noting that the RHS telescopes to $0$ reveals the desired recursive relation.

The above proof-technique is called the Wilf-Zeiberger methodology.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.